Video Lesson Tutorial: An Innovative Strategy in Improving Students’ Learning Skills in General Chemistry - RODEL AZARES (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
This study addresses the need for pedagogical innovation by evaluating the effectiveness of teacher-made video lessons combined with learners' activity sheets (LAS) on the performance of STEM students. The background of this research is rooted in the challenge of mastering difficult learning competencies, necessitating the development of an enhancement plan based on targeted interventions. The primary objective was to determine whether the integration of these digital and printed resources significantly improves student learning outcomes in complex subject matter. The researcher employed a quasi-experimental research design to gather data. The methodology involved identifying the least learned competencies and developing localized video lessons to address them. Data were gathered from STEM respondents via pretests and posttests, in addition to the provision of learners' activity sheets to promote interactive learning. The results, as reflected in the statistical analysis, revealed a substantial increase in student performance. The pretest mean score of 2.90 rose significantly to a posttest mean score of 12.30 following the intervention. Statistical testing yielded a calculated t-value of -28.85 and a p-value of .000, which is well below the 0.05 significance level. This indicates a statistically significant difference, leading to the rejection of the null hypothesis. The negative t-value further confirms that posttest scores were significantly higher than pretest scores. In conclusion, the integration of teacher-made video lessons and activity sheets is highly effective in improving STEM students' academic performance, suggesting that learners respond positively to diverse, modern techniques when tackling challenging topics.